توظيف وسائل التكنولوجيا الحديثة في الدعوة إلى الله تعالى - بن الشايب, جهاد; حنكه, حدي; عوينات, مروه (My University, 2017)
إن د ا رسة تكنولوجيا الدعوة تصل بنا في نهاية الأمر إلى مفهوم شامل لتكنولوجيا الدعوة الإسلامية، وهذا المفهوم ينطلق من أسس ثلاثة، هي: "كون تكنولوجيا الدعوة الإسلامية )مجالً (، وكونها )عملية(، وكونها )مهنية(". والنظر إلى تكنولوجيا الدعوة )كمجال( ما هو إل محاولة علمية جادة لتحديد مكونات هذا التخصص، وبيان ملامحه الأساسية من أجهزة حديثة، ووسائل تخزين، وقوى بشرية، وتصميم، وانتاج، وتقويم، مع إطار نظري وخطط دعوية. أما تكنولوجيا الدعوة الإسلامية كعملية فهي أكبر من مجرد إدخال المستحدثات - - التكنولوجية إلى المجال الدعوي؛ بل هي مخططة ومنظمة، فريدة، وفعالة، وتخضع للد ا رسة الكاملة لكل المكونات السابقة المرتبطة بالمجال. ومن الطبيعي أن النظر إلى تكنولوجيا الدعوة الإسلامية كمجال وكعملية يحتم علينا النظر إليها كمهنة، إذ أن أي مجال به - - مجموعة من العمليات يتطلب أن يكون هناك من يقوم به، وهم الممتهنون لهذه المهنة، وهذا ما يؤكد أن العمل في مجال تكنولوجيا الدعوة الإسلامية يتطلب أف ا ردًا مُ عًًَدّين إعدادًا جيدًا، وأصحاب مها ا رت خاصة وقد ا رت عالية في التعامل مع المكونات المعروفة لمجال تكنولوجيا الدعوة الإسلامية. إن وسائل التصالت الحديثة إذا ما نظرنا إليها بمنظور إسلامي تدور في محاور - - ثلاثة: أولها: أنها تُع د آية دالة على صدق النبوة المحمدية. ثانيًا: أنها فرصة عظيمة لنشر هذه الدعوة. ثالثًا: أنها تعد تحديًا كبي اً ر يواجه الدعوة في هذا العصر. أما كونها آية، فلأنها جعلت بلدان العالم جميعها بمثابة البلد الواحد، التي كان يرسل إليها كل نبي على حده، وفي هذا دللة على أن الذي أرسل سيدنا محمدًا للناس كافة وهو - الخالق سبحانه كان يعلم بلا شك أن العالم كله سيصير بمنزلة القرية الواحدة فلا - - - يحتاج الأمر إلى تعدد المرسلين. وفي هذا دليل واضح يضاف إلى الأدلة الكثيرة المشيرة إلى صدق رسولنا المعصوم صلى الله عليه وسلم، وأنه خاتم الأنبياء والمرسلين. أما كون هذه الوسائل الحديثة فرصة عظيمة لنشر الدعوة الإسلامية، فهذا أمر ل يكاد يحتاج إلى بيان، فقد تطورت آليات الطباعة والنشر على مواد مطبوعة، وغير مطبوعة كما نرى، والكلمة المنطوقة لم يعد ينتهي تأثيرها بانتهاء النطق بها؛ بل صارت مسجلة على ش ا رئط تسجيل مسموعة وأخرى مرئية مسموعة، وظهرت الشبكة العالمية للمعلومات )الإنترنت(. وأما كونها تحديًا عظيمًا، فأولً : لأنها كما أتاحت لنا إيصال الدعوة الإسلامية إلى غير المسلمين في بقاع الأرض، فقد سهلت لغير المسلمين إيصال سمومهم إلينا، وبما أن إمكاناتهم المادية، واد ا ركهم لأهمية هذه الوسائل أكبر منا، فإن ما ينجحون في توصيله إلينا أكثر بكثير مما ننجح في إيصاله إليهم، وثانيًا: لأننا لم نضع حتى الآن آليات تنفيذية مخططة وفق متطلبات هذا العصر؛ من أجل الدفاع عن هذا الدين ودعوة البشرية إليه. Research Summary The study of advocacy technology ultimately reaches us with a comprehensive concept of Islamic da'wah technology. This concept is based on three principles: "The fact that Islamic call technology is an area, that it is practical and that it is professional ". To consider the technology of advocacy as a field is a serious scientific attempt to identify the components of this specialization, and to describe its basic features of modern devices, storage devices, human resources, design, production and evaluation, with a theoretical framework and advocacy plans . The technology of Islamic da'wah - as a process - is more than just introducing technological innovations into advocacy; it is planned, organized, unique, effective and subject to full study of all previous components associated with the field. It is natural to consider the technology of Islamic da'wa - as a field and as a process - that we must consider as a profession, since any area with a range of operations requires that there be those who do, who are professionals of this profession, which confirms that work in the field of Islamic call technology requires Well-equipped individuals with special skills and capabilities in dealing with the well-known components of Islamic advocacy technology . The modern means of communication - if we look at it with an Islamic perspective - revolves around three axes : First: it is a verse of the validity of the Prophet Muhammad . Second, it is a great opportunity to spread this call . Third: It is a great challenge facing the call in this age . As a sign, it made all the countries of the world the same country, to which every prophet was sent, and this is an indication that the one who sent Muhammad to all the people - the Creator, the Almighty - knew without a doubt that the whole world would become like the village One does not require the multiplicity of senders . In this clear evidence is added to the many evidence pointing to the truth of our Messenger infallible peace be upon him, and that the seal of prophets and messengers . As for the fact that these modern means are a great opportunity to spread the Islamic call, this is hardly necessary. The mechanisms of printing and publishing have developed on printed, non-printed materials as we see. The spoken word no longer ends with the end of its pronunciation; And other visual audible, and emerged the World Wide Web (Internet .) As it is a great challenge, firstly: because it also allowed us to deliver the Islamic call to non-Muslims in all parts of the world, it facilitated the non-Muslims to deliver their poison to us. As their material potential and awareness of the importance of these means is greater than us, We succeed in delivering it to them, and second: because we have not yet put in place executive mechanisms planned in accordance with the requirements of this age; in order to defend this religion and call humanity to it .
دعوة